2019
DOI: 10.1016/j.celrep.2019.01.111
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Pum1 and Pum2 Control Body Size via Translational Regulation of the Cell Cycle Inhibitor Cdkn1b

Abstract: SUMMARY Body and organ size regulation in mammals involves multiple signaling pathways and remains largely enigmatic. Here, we report that Pum1 and Pum2 , which encode highly conserved PUF RNA-binding proteins, regulate mouse body and organ size by post-transcriptional repression of the cell cycle inhibitor Cdkn1b . Binding of PUM1 or PUM2 to Pumilio binding elements (PBEs) in the 3 ’ UTR of Cdkn1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 53 publications
2
51
0
1
Order By: Relevance
“…Pum2 mutant ESCs were reported to have no obvious defects in self-renewal or differentiation (24). Correspondingly, Pum2 mutant mice were viable and fertile with only smaller testes (25) and subtle neurological defects in memory, nesting behavior, and an increased propensity to seizures (24,26). Similarly, little is known about the function of Pum1.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Pum2 mutant ESCs were reported to have no obvious defects in self-renewal or differentiation (24). Correspondingly, Pum2 mutant mice were viable and fertile with only smaller testes (25) and subtle neurological defects in memory, nesting behavior, and an increased propensity to seizures (24,26). Similarly, little is known about the function of Pum1.…”
Section: Significancementioning
confidence: 99%
“…Pum1 has also been implicated in human neurodegeneration and motor ataxia (28,29) and in the maintenance of genomic stability in mice (30). Recent work showed that decreasing the number of Pum1 + and/ or Pum2 + alleles reduces body size in a dose-dependent manner, partly due to translational derepression of the cell-cycle inhibitor CDKN1B (26) and that complete deficiency of Pum1 and Pum2 leads to embryonic lethality (31). Conditional knockout of Pum1 and Pum2 in the nervous system affects neural stem-cell maintenance by derepressing the translation of many mRNAs (32,33).…”
Section: Significancementioning
confidence: 99%
“…Removing cki-2 partially rescues the germline stem cell depletion phenotype in fbf-1 fbf-2 double mutant adult hermaphrodites (Kalchhauser et al, 2011), suggesting that repression of cki-2 is not the only mechanism by which FBFs promote stem cell proliferation. CIP/KIP family cyclin-dependent kinase inhibitors are conserved targets of PUF proteins as they were found to be regulated by PUFs in mouse embryos and human cells (Kedde et al, 2010;Lin et al, 2019). Interestingly, genes encoding diverse cell cycle regulators, beyond cki-2 and its homologs, are enriched among target mRNAs pulled down with FBFs as well as PUF proteins from other organisms (Hafner et al, 2010;Kershner and Kimble, 2010;Chen et al, 2012;Prasad et al, 2016;Porter et al, 2019), suggesting a conserved mechanism of PUF-mediated control of cell proliferation.…”
Section: Regulatory Roles Of Puf Proteins In C Elegans Germline Stemmentioning
confidence: 99%
“…Pum2 mutant ESCs were reported to have no obvious defects in self-renewal or differentiation (22). Correspondingly, Pum2 mutant mice were viable and fertile with only smaller testes (23) and subtle neurological defects in memory, nesting behavior, and as well as increased propensity to seizures (22,24). Similarly, little is known about the function of Pum1; conditional knockout of Pum1 in the mouse testis results in decreased fertility (25).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, little is known about the function of Pum1; conditional knockout of Pum1 in the mouse testis results in decreased fertility (25). Recently, Pum1-Pum2 double mutant been shown to be embryonic lethal (26) and that Pum1 and Pum2 deficiencies reduces body size in a dose-dependent manner, partly due to translational de-repression of the cell cycle inhibitor CDKN1B (24).…”
Section: Introductionmentioning
confidence: 99%